Lead-induced oxidative stress triggers root cell wall remodeling and increases lead absorption through esterification of cell wall polysaccharide - Zhang, Jing; Qian, Yiguang; Chen, Zhongbing; Amee, Maurice; Niu, Hong; Du, Dongyun; Yao, Jun; Chen, Ke; Chen, Liang; Sun, Jie (Journal of hazardous materials, 2020)
Tall fescue (Festuca arundinacea Schreb) shows remarkable tolerance to lead (Pb), but the mechanisms involved in metal tolerance are not yet well understood. Here, tall fescue were firstly cultivated hydroponically with Pb2+ (0, 50, 200 and 1000 mg/L) for 14 days. The results showed that remodeling of root architecture plays important roles in tolerance of tall fescue to Pb2+ stress. Increased cell wall (CW) components contribute to restrict high amount of Pb2+ in roots. Additionally, the uronic acid contents of pectin, hemicellulose 1 (HC1) and hemicellulose 2 (HC2) increased under Pb2+ stress. We further observed that tall fescue cultivated with H2O2 showed similar remodeling of root architecture as Pb2+ treatment. Furthermore, pectin, HC1 and HC2 fractions were sequentially extracted from 0 and 10 mM H2O2 treated roots, and Pb2+ adsorption capacity and contents of carboxyl groups of pectin and HC2 fractions were steadily increased under H2O2 treatment in vitro. Our results suggest that degrees of esterification of pectin and HC2 are regulated by H2O2. High amount of low-esterified pectin and HC2 offer more carboxyl groups, provide more Pb2+ binding sites, and restrict more Pb2+ in the CW, which may enhance tolerance of tall fescue to Pb2+ stress.
Keywords: látky znečišťující půdu; Oxidative Stress; Cell Wall; Lead; kořeny rostlin; reaktivní formy kyslíku; Plant Roots; Polysaccharides; Reactive Oxygen Species; buněčná stěna; Soil Pollutants; Festuca; olovo; esterifikace; Esterification; oxidační stres; polysacharidy